Simulation of failure in laminated polymer composites: Building-block validation. (15th October 2019) - Furtado, C.; Catalanotti, G.; Arteiro, A.; Gray, P.J.; Wardle, B.L.; Camanho, P.P.
Abstract: The development of numerical tools to complement the experimental determination of structural design parameters is of key importance to hasten the certification process of new materials and structures. In this work, a methodology to simulate elastic and inelastic deformation of composite laminates at the subcomponent level based on finite element analysis is proposed. A modified version of a continuum damage model proposed in the literature combined with a frictional cohesive zone model is used to capture the intralaminar and interlaminar damage and failure of composite laminates in general loading conditions. The methodology is validated for three aerospace-grade carbon fibre reinforced (epoxy) polymer composite material systems and coupon configurations with increasing level of complexity, including unnotched tension/compression, open-hole tension/compression and filled hole compression. The predictions obtained are in good agreement with the experimental results for all the test cases, oftentimes within the standard error of the tests, with a maximum relative error of 13%.